The Development of Brand Equity Measurements for Competitiveness of Thai Seafood Industry in Consumers-Perspective - Jitprapai, Nutthapon; Kittisaereekul, Sidanuch (Journal of Applied Informatics and Technology, 2025)
The study aimed to develop a precise measurement of brand equity for the Thai seafood industry, specifically focusing on canned tuna and shrimp products, from a consumer perspective. It utilized a comprehensive mixed-methods approach that combined qualitative interviews with experts and a quantitative survey of 500 consumers, following Churchill’s recommendations. The structural validity of the research variable measurement was tested. Research Findings: The study revealed a consumer-oriented brand measurement model comprising four key components: brand loyalty, brand awareness, brand perceived quality, and brand association. This model provides valuable insights for assessing and generalizing brand equity within the Thai canned tuna and shrimp market. Theoretical Contribution/Originality: This research contributes significantly by offering a reliable measurement of brand equity for canned tuna and shrimp brands in Thailand. The comprehensive model, encompassing brand loyalty, awareness, perceived quality, and association, holds practical implications for marketers and practitioners aiming to enhance brand equity within the industry.